Recepcja Ojców Kościoła w "Confessio catholicae fidei christiana" Stanisława Hozjusza - Wysocki, Marcin (Vox Patrum, 2016)
Among the famous people related to Warmia one of the most prominent is undoubtedly the bishop of Warmia, Cardinal Stanislaus Hosius, a famous diplomat, humanist, lawyer, poet, illuminator scientific life in Warmia, but also a theologian and defender of the Catholic faith. His theological views and his defending of the faith against the reformers are included in a number of his writings, but the greatest influence and fame had his work Confessio catholicae fidei Christiana (Christian profession of the Catholic faith). It was written as an extension of a creed created on request of participants of the Council in Piotrków (1551), who turned to Hosius with request to write a short statement of the most important truths of the Catholic faith. In his work Hosius many times repeatedly referred to the argument from Tradition and he used the writings of the early Christian writers. The article is an attempt to explore how Hosius, arguing with Protestants, uses patristic argument and how he uses the writings of early Christian writers. The article presents as well the idea of the reception of the Fathers of the Church in the most important work of Hosius.